Characteristics of Anaplastic Oligodendrogliomas Short-Term Survivors: A POLA Network Study. (5th March 2022) - Garnier, Louis; Vidal, Chrystelle; Chinot, Olivier; Cohen-Jonathan Moyal, Elisabeth; Djelad, Apolline; Bronnimann, Charlotte; Bekaert, Lien; Taillandier, Luc; Frenel, Jean-Sébastien; Langlois, Olivier; Colin, Philippe; Menei, Philippe; et al.
Abstract : Anaplastic oligodendrogliomas (AO) are rare brain tumors, accounting for approximately 5% of adult gliomas and 0.5% of all primary tumors affecting the central nervous system. This article reports results of a study conducted within the frame of the French POLA network on the characteristics of survivors of AO, comparing populations with a disease-specific survival of less than 5 years with populations with a survival 5 years or more. Abstract: Background: Anaplastic oligodendrogliomas IDH -mutant and 1p/19q codeleted (AO) occasionally have a poor outcome. Herein we aimed at analyzing their characteristics. Methods: We retrospectively analyzed the characteristics of 44 AO patients with a cancer-specific survival <5 years (short-term survivors, STS) and compared them with those of 146 AO patients with a survival ≥5 years (classical survivors, CS) included in the POLA network. Results: Compared to CS, STS were older ( P = .0001), less frequently presented with isolated seizures ( P < .0001), more frequently presented with cognitive dysfunction ( P < .0001), had larger tumors ( P = .= .003), a higher proliferative index ( P = .= .0003), and a higher number of chromosomal arm abnormalities ( P = .= .02). Regarding treatment, STS less frequently underwent a surgical resection than CS ( P = .= .0001) and were more frequently treated with chemotherapy alone ( P = .= .009) or with radiotherapy plus temozolomide ( P = .= .05). Characteristics independently associated with STS in multivariate analysis were cognitive dysfunction, a number of mitosis > 8, and the absence of tumor resection. Based on cognitive dysfunction, type of surgery, and number of mitosis, patients could be classified into groups of standard (18%) and high (62%) risk of <5 year survival. Conclusion: The present study suggests that although STS poor outcome appears to largely result from a more advanced disease at diagnosis, surgical resection may be particularly important in this population.